Conversion of l‐Tryptophan Derivatives into Biologically Active Amino Acid Ionic Liquids. Issue 22 (14th June 2021) - Szymaniak, Daria; Kleiber, Tomasz; Wojcieszak, Marta; Materna, Katarzyna; Pernak, Juliusz
Abstract: Natural auxins are a group of plant hormones that affect plant growth and development. The most common auxin is indole‐3‐acetic acid (IAA), which is mainly synthesized from tryptophan. Since converting synthetic auxins into an ionic liquid increases their herbicidal activity, an attempt was made to synthesize new amino acid ionic liquids (AAILs) with l ‐tryptophanate anions. As a result of the synthesis, two homologous series, tetraalkylammonium l ‐tryptophanates and dialkyldimethylammonium l ‐tryptophanates, were obtained with yields exceeding 95 %. For the obtained AAILs, basic physicochemical properties (solubility in solvents of different polarity, thermal stability, phase changes, and surface activity) were determined, and whether the obtained salts act as growth stimulants for lettuce ( Lactuca sativa L.) was evaluated. The transformation of l ‐tryptophan into AAILs improved the physicochemical properties and increased the auxin activity. In addition, the higher content of nutrients (micro‐ and macroelements) made lettuce a healthier food product. Abstract : This study presents the preparation and characterization of new amino acid ionic liquids based on l ‐tryptophan. Converting l ‐tryptophan into an ionic form improved its physicochemical properties, such as solubility in water and organic solvents, thermal stability, surface activity and auxin activity. The obtained amino acid ionic liquids (AAILs) and quaternary ammonium salts (QASs) increased the yield of the tested lettuce as well as the content of nutrients, which made the lettuce a healthier food product.